2021
DOI: 10.3389/fimmu.2021.635471
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Modulation of the Gut-Lung Axis in COVID-19

Abstract: COVID-19 is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), and according to the World Health Organization (WHO), to date, SARS-CoV-2 has already infected more than 91.8 million people worldwide with 1,986,871 deaths. This virus affects mainly the respiratory system, but the gastrointestinal tract (GIT) is also a target, meanwhile SARS-CoV-2 was already detected in oesophagus, stomach, duodenum, rectum, and in fecal samples from COVID-19 patients. Prolonged GIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 148 publications
(164 reference statements)
3
152
0
13
Order By: Relevance
“…Overall, the data presented here suggest a correlation between HOM dysbiosis and individual susceptibility to SARS-CoV-2 severe infection, indicating an interplay between HOM profile (including mycobiome and virome), inflammation, and mucosal IgA response. If HOM alteration is the cause or effect of severe COVID-19, it is not currently possible to distinguish, because the presence of SARS-CoV-2 in the oral cavity may impact microbiome dysbiosis ( Xiang et al, 2020 ; de Oliveira et al, 2021 ). On the other hand, connections between oral dysbiosis and post-viral complications have been reported, suggesting that improving oral health may reduce the risk of complications from COVID-19 ( Sampson et al, 2020 ), thus supporting the hypothesis of a role of dysbiosis in the virus-induced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the data presented here suggest a correlation between HOM dysbiosis and individual susceptibility to SARS-CoV-2 severe infection, indicating an interplay between HOM profile (including mycobiome and virome), inflammation, and mucosal IgA response. If HOM alteration is the cause or effect of severe COVID-19, it is not currently possible to distinguish, because the presence of SARS-CoV-2 in the oral cavity may impact microbiome dysbiosis ( Xiang et al, 2020 ; de Oliveira et al, 2021 ). On the other hand, connections between oral dysbiosis and post-viral complications have been reported, suggesting that improving oral health may reduce the risk of complications from COVID-19 ( Sampson et al, 2020 ), thus supporting the hypothesis of a role of dysbiosis in the virus-induced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes such as Faecalibacterium prausnitzii , Eubacterium rectale , and several bifidobacterial species known for their immunomodulatory roles were depleted in patients with COVID-19 [ 109 ]. This dysbiosis directly correlated with COVID-19 severity and persistent infection of SARS-CoV-2 in the gut epithelium [ 110 ]. Moreover, studies identify a crucial link between the gut microbiome and lung health, coined by the term “gut–lung axis,” where gut dysbiosis was associated with ARDS development [ 111 , 112 ].…”
Section: Metformin Intervention In Covid-19mentioning
confidence: 99%
“…The potential application of probiotics for the prevention and treatment of COVID-19 will probably be extensively investigated in the future, and several reviews also address the question of whether probiotics could be used as possible adjuvant therapy in the prophylaxis and/or alleviation of COVID-19 symptoms [66,[86][87][88]. The main basis for this possibility is that several clinical studies have reported alterations of gut microbiota/dysbiosis of COVID-19 patients [89][90][91], and it is well-known that probiotics are efficient in positively modulating the gut microbiome in many cases of dysbiosis as has been noted in systematic reviews and meta-analyses [92][93][94][95]. To date, one clinical study has addressed this question, and it concluded that support for further trials to assess the potential role of probiotics in preventing viral URTI (and possibly also COVID-19) is warranted [96].…”
Section: Discussionmentioning
confidence: 99%